Can we do without biocides to cope with biofilms and lichens on stone heritage?. (August 2022) - Pinna, Daniela
Abstract: In the past several years, products and methods alternative to conventional biocides, used in the conservation of cultural heritage objects, have been investigated increasingly to eradicate or prevent the growth of microorganisms and lichens on stone artworks. Although some concerns about conventional biocides are legitimate, the "run" to alternative substances is growing concern as well. This review aims at contributing to the interpretation of recent findings in innovative methods and substances focusing on i) resistance of biofilms to environmental stressors, including antimicrobials; ii) metals and metal-based compounds including nanoparticles; iii) mixtures of metal nanoparticles and metal oxides with water repellents and consolidants; iv) natural compounds (essential oils of plants, secondary metabolites of lichens, microbial by-products, microorganisms, extracts from marine organisms); v) toxicity of essential oils; vi) alternative chemicals (Ionic liquids, dimethyl sulfoxide gel, hydrolase enzymes). This review also includes a discussion on the advantages, drawbacks and limitations of the examined studies to encourage a constructive discussion among professionals involved in the field of stone heritage conservation, and to develop a sustainable path for managing the biological colonization. This state-of-the-art review indicates that further research is needed to propose alternative compounds to conventional biocides. Highlights: Review of innovative substances experimented against microbial colonization on heritage stone. Biofilms tolerate environmental stressors to adapt and survive in harmful environments. Metals and metal-based compounds, metal nanoparticles, natural compounds and alternative chemicals are discussed. Antimicrobial activity of nanoparticles is linked to their dimensions and method of synthesis. Concerns about toxicity of substances alternative to conventional biocides.